REPRESENTASI KEKERASAN SEKSUAL PADA PEREMPUAN (Studi Analisis Semiotika dalam Film â7 Hati 7 Cinta 7 Wanitaâ) - Valerina, Wisti (KOMUNITAS, 2013)
The globalization implies the existence of an infinite information. Furthermore, the audience themselvesÂ toÂ beÂ smartÂ inÂ choosingÂ andÂ receiveÂ informationÂ onÂ getÂ it.Â OneÂ ofÂ mediumÂ isÂ film. Various types of films that update will become a factor in the audience to absorb the information that is in the vicinity. Information about sexual violence on women, for example, will always be a hot topic discussed due to rampant cases of sexual violence involving women as victims. This study aims to determine the sexual assault case that represented in the film â7 Hati 7 Cinta 7 Wanitaâ. ThisÂ caseÂ mayÂ beÂ existingÂ inÂ ourÂ neighbourhood.Â ThisÂ filmÂ givesÂ taughtÂ toÂ women,Â especially Indonesian women not to dissolve into the feelings and in the end only be a mere victim. ThisÂ researchÂ isÂ aÂ qualitativeÂ studyÂ usingÂ semiotic analysis.Â Â ResearchÂ showsÂ thatÂ filmÂ â7 HatiÂ 7Â CintaÂ 7Â WanitaâÂ hasÂ fiveÂ elementsÂ ofÂ sexualÂ violenceÂ onÂ womenÂ byÂ theÂ National CommissionÂ onÂ ViolenceÂ AgainstÂ WomenÂ (KomnasÂ Perempuan)Â whichÂ isÂ probablyÂ theÂ result representationÂ ofÂ whatÂ isÂ aroundÂ us.Â FiveÂ elementsÂ are:Â (1Â )Â SexualÂ Harassment,Â (2)Â Sexual Torture, (3) Abortion Coercion, (4) Forced Marriage,Â and (5) TraffickingÂ ofÂ Women forÂ Sexual Purposes. The five elements, perhaps even to the 15elements of sexual violence on women already in the grade by the National Commission for Women are there around us.